The Influence of Nutrition, Clean Water, and Hand Hygiene on Stunting Incidences - Maulida Nurfazriah Oktaviana; Fiqi Khoirur Roziqin; Firdawsyi Nuzula (Gema Lingkungan Kesehatan, 2025)
Among the nutritional problems affecting toddlers that have not yet been fully resolved, they can result in failure to grow and develop, which can lead to stunting. The prevalence of stunting tends to decrease every year, but the decline is still not substantial. This research aims to identify the influence of nutrition, clean water, and hand hygiene on the incidence of stunting. The research used was an analytical correlation. The research design was cross-sectional. There were 130 participants in this research sample. The Chi-square bivariate analysis data and multivariate analysis using ordinal logistic regression. The results of the bivariate analysis showed that the most frequent cases of stunting were very short, with 81 cases (62%). Statistically, there is a significant relationship between nutrition (p = 0.000), clean water (p = 0.000), and hand hygiene (p = 0.004) with the incidence of stunting. Multivariate analysis shows that clean water has a most dominant effect on nutritional status with a Wald value of 17.290. Insufficient nutritional intake, unavailability of clean water, improper hand hygiene can cause stunting. Improvement in these three factors is very important to reduce the prevalence of Stunting and improve the nutritional status of children in the study area. The government and health organizations must increase public awareness with nutritional programs, clean water sanitation and getting used to hand hygiene.